Sea surface circulation variability in the Ionian-Adriatic Seas. (November 2020) - Kalimeris, Anastasios; Kassis, Dimitris
Highlights: The sea-surface circulation variability in the Ionian-Adriatic region is studied. Two alternative circulation indices are used to quantify the surface current variations. The circulation sense and strength is analyzed over a period of 60 years. The significant variability modes of the surface circulation are resolved. Circulation regime shifts associated with different dynamical epochs are detected. Abstract: The surface circulation of the Ionian and Adriatic Seas is explored by the re-analysis of available datasets that estimate the mean monthly ocean state for the 60 years-long time period 1955–2015. Emphasis is given to the major recurrent and transitional events in the area. Two circulation indices are utilized for the quantification of the cyclonic or anticyclonic circulation modes and intensity, one based on the vorticity flux of the reconstructed mean monthly surface velocity field, and another based on an appropriately modified version of the velocity field. Such quantification consequently allows for a detailed analysis of the surface circulation variability for the entire Ionian and Adriatic basins, as well as for sub-regions of particular interest. Discontinuities associated with possible regime shifts of the examined flow field were identified by time-series analysis of the circulation indices and compared to well-documented events in the hydrography of the studied area. Subsequently, the statistically significant components of the surface circulation variability were resolved out of a red noise background in the time–frequency domain and their evolution was studied. The results highlight the presence of various circulation modes and reversals in different temporal scales (mainly seasonal and decadal to inter-decadal) which are discussed in reference to the dynamics of both the sub-regional (Western, Northern, Eastern, and Southern Ionian, as well as Northern and Southern Adriatic), and of the basin-wide (Ionian or Adriatic) spatial scales. The relationships of the surface circulation variability between the Ionian and the Adriatic basins are also assessed through wavelet coherence.